Racism and xenophobia: The role of the Church in South Africa - Pillay, Jerry (Verbum et ecclesia, 2017)
Racism and xenophobia have become a worldwide issue and challenge. The recent flood of immigrants and refugees into Europe and America has put this matter on the world map. In South Africa racism and xenophobia have, in recent times, reached explosive proportions and have greatly intensified the need for the Church to get more deeply involved in the creation of racial harmony and peace as it works towards the fullness of life for all people. This chapter explored the challenges of racism and xenophobia in South Africa and concluded by discussing the role of the Church in combating these realities.